A Phenomenological Inquiry of the Lived Experiences of Male Homosexual - Arini, Larasuci; Hamid, Achir Yani S; Fernandes, Feri; Syarli, Setiadi (Jurnal Keperawatan Soedirman, 2020)
The number of homosexuals in Indonesia continues to rise each year. In Padang, there were 662 men with gay sexual orientation. This qualitative study aimed to determine the practice of life as homosexuals. This phenomenological study described the lived experience of men with homosexuality. The participants of this study were six men with same-sex sexual orientation who lived in Padang and could communicate in Bahasa or Minangnese language. They were collected using snowball sampling techniques. The results of this study were analyzed using the Colaizzi method. The results of this study obtained eight themes, namely the causes of same-sex relationships, early experiences in relationships, the process of partner selection, potential physical and psychosocial problems, self-concept of sexual orientation, the roles of parents and mothers, and stabilization of gender status choices. Of these 8 themes, the initial causes of having a relationship were the most dominant experiences.Â  All participants expressed the beginning of being homosexual just for fun, starting pleasure, and influenced by friends. Besides, the relationship process such as how to get a partner, location, and sexual relationship constraints in most participants had also included in the discussion.